2022
DOI: 10.3390/plants11233309
|View full text |Cite
|
Sign up to set email alerts
|

Varietal Descriptors for the Distinction of Underutilized Varieties of Sechium edule (Jacq) Swartz

Abstract: Sechium edule (Jacq.) Sw. (Cucurbitaceae) is a species native to Mexico and Central America. The collection, characterization, and evaluation of accessions maintained in genebanks is essential for the conservation of this species. However, there are no specific varietal descriptors that differ from those used in a phenetic approach and are adapted to international registration guidelines to help distinguish, improve, cluster, and protect intraspecific variants of common use and those obtained by breeding. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, it is necessary to increase the number of samples, expand the geographic sampling range, and utilize more informative markers (i.e., Single Nucleotide Polymorphisms, SNPs) to assess the chayote genetic diversity and morphological variation. Our study also established preliminary information to develop research to understand the response of chayote under different environments and management (i.e., commercial, cultural, and conservation) [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is necessary to increase the number of samples, expand the geographic sampling range, and utilize more informative markers (i.e., Single Nucleotide Polymorphisms, SNPs) to assess the chayote genetic diversity and morphological variation. Our study also established preliminary information to develop research to understand the response of chayote under different environments and management (i.e., commercial, cultural, and conservation) [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Germplasm National Bank of Sechium edule (BANGESe) has been established in Mexico, with most accessions originating from backyard areas. Reproductive isolation of most wild chayote materials has been influenced by consumer preferences [ 12 ]. To date, China has not carried out a systematic germplasm collection of chayote.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the varying availability periods of chayote fruits across different regions and the fact that chayote is propagated through its fruits, traders are able to transfer popular local varieties from one planting area to another with ease [ 10 ]. Furthermore, 223 pairs of AFLP molecular markers were utilized to analyze 133 accessions of chayote resources from Mexico, revealing a high degree of genetic polymorphism between cultivated germplasm and their wild ancestors [ 12 ]. Moreover, the study showed that eight pairs of polymorphic SSR primers were screened from 20 chayote in Mexico by using 11 SSR markers developed, which will be helpful to characterize the population genetic structure of chayote varieties in Mexico and Latin America and decipher the dynamics of their genetic diversity [ 20 ].…”
Section: Introductionmentioning
confidence: 99%